An outbreak of tuberculosis in endangered northern pig‐tailed macaques (Macaca leonina) and milu deer (Elaphurus davidianus) from a zoo in China. Issue 2 (10th January 2023) - Chen, Yingyu; Yan, Yu; Gao, Yanhong; Li, Yurui; Zhang, Kailun; Zhou, Min; Sun, Liang; Wang, Yu; Robertson, Ian Duncan; Guo, Aizhen
Abstract: Background: Tuberculosis (TB) is a zoonotic disease that affects humans and domesticated and wild animals. Animals in zoos are potentially an important source of TB for humans; however they are often neglected in routine disease surveillance programs. This investigation reports an outbreak of TB in milu deer and northern pig‐tailed macaques in a zoo in Wuhan, China, which highlighted the need for improved prevention and control of TB in China. Methods: Between 24 November and 9 December 2020 two milu deer and a northern pig‐tailed macaque that were displaying signs of wasting died. Post‐mortem, histopathological diagnosis and acid fast staining were used for the dead animals. Multiple PCR for Mycobacterium tuberculosis complex (MTBC) was performed to identify the bacterial in both milu deer and northern pig‐tailed macaque. The serum antibody iELISA for MTBC was then performed for all the surviving milu deer and northern pig‐tailed macaques. Six seropositive milu deer and a seropositive northern pig‐tailed macaque were subsequently euthanised and, along with two other dead milu deer, necropsied. DNA from these tissue samples was extracted and detected MTBC using PCR and Real‐time PCR. Subsequently bacterial isolation was used to confirm the infection. Results: The lungs of the dead animals displayed gross and histological TB‐like lesions and changes, and red staining bacilli were detected in smears of the lesions by microscopy after acid fast staining. Mycobacterium bovis ( M. bovis ) was detected in the two milu deer and Mycobacterium tuberculosis ( M. tb ) in the northern pig‐tailed macaque using multiple PCR for MTBC. 35.3% surviving milu deer and 50% surviving northern pig‐tailed macaques MTBC serologically positive. Six of the euthanised milu deer were also positive on a DNA test for M. bovis and the euthanised northern pig‐tailed macaque was positive to M. tb . Conclusions: This is the first report of tuberculosis in the endangered species, milu deer and northern pig‐tailed macaques, in China, and warrants urgent attention by researchers and conservation authorities. These cases highlight the need for expanding surveillance for MTBC to zoos in China. Abstract : Zoonotic tuberculosis (TB) affects humans and domesticated and wild animals. Milu deer and northern pig‐tailed macaque was found to be infected with Mycobacterium bovis ( M. bovis ) and Mycobacterium tuberculosis ( M. tb ), respectively by multiple PCR and DNA test. Serological test showed a 35.3% and 50% testing positive rate of the surviving milu deer and northern pig‐tailed macaques, respectively. This is the first report of tuberculosis in the endangered species, milu deer and northern pig‐tailed macaques, in China, and warrants urgent attention by researchers and conservation authorities.